Assessment of Physicochemical and Fatty Acid Properties of Oils Extracted from Avocado Pear (Persea americana) and African Black Pear (Dacryodes edulis) - Nwachukwu, Chinwe Adaobi; Okoronkwo, Theresa Odinakachi; Arukwe, Dorothy Chinomnso (Journal of Agriculture, Food Technology and Sustainability, 2024)
The aim of this study was to assess the physicochemical and fatty acid properties of the oils extracted from avocado pears and African black pears harvested from University of Agriculture Umuagwo. The physical and chemical and fatty acid properties, including oil yield, refractive index, specific gravity, flash point, melting point, viscosity, iodine value, free fatty acid value, saponification value, and peroxide value, were measured. Each analysis was performed in triplicate, and results were analysed using ANOVA Regression analyses of data were conducted. Significant differences among the means were established at (p<0.05) using Duncan’s multiple range test. Some parameters under physical properties did not differ (p>0.05) significantly; pH value for avocado pear oil was 6.94 while that of African pear oil was 6.91, Moisture content for AVPO was 0.51% while that of ABPO was 0.51. There were significant (p<0.05) differences in most of the parameters due to specie difference. Free fatty acid value for AVPO-0.526% and that of ABPO- 0.587%. The fatty acids found in avocado oil are predominantly monounsaturated, with smaller amounts of polyunsaturated and saturated fatty acids, while the fatty acid profile of African Black Pear oil revealed it as a good source of monounsaturated fats and some essential polyunsaturated fats. Results obtained showed that avocado pear oil and African black pear oil conformed to standards set by Nigeria Industrial Standards and Standard Organization of Nigeria for vegetable oils and can be used as edible oils and can serve industrial purposes as well.